AODV protocol for acoustic-radio integrated network based on location information and energy balance - Nongyu WEI; Zilong JIANG; Fangjiong CHEN (物联网学报)
Different from terrestrial internet of things (IoT) applications, marine IoT applications need to solve the problem of information interaction between surface network and underwater network.The key to solve this problem is to design a proper routing scheme.An ad hoc on-demand distance vector for acoustic-radio integrated network (AR-AODV) was proposed based on location information and energy balance.The protocol enables surface radio links to forward more information data, so as to reduce the burden of underwater communication network and improve the overall performance.In the proposed protocol, the forwarding priority of the buoy nodes was higher than that of the underwater nodes.When the source node needs to send data, it enters the route discovery phase, i.e., the node uses its position and energy information as the heuristic information to calculate the forwarding probability and broadcast route request (RREQ) packets.When the destination node receives an RREQ packet, it sent an RREP packet to update the pheromone and select the optimal path based on the pheromone.Compared with AODV protocol, AR-AODV protocol has significantly improved the performance in terms of transmission success rate, transmission delay, throughput, energy conversion rate and routing packet forwarding times.